1997
DOI: 10.1111/j.1365-2044.1997.122-az0116.x
|View full text |Cite
|
Sign up to set email alerts
|

Public perceptions of postoperative pain and its relief

Abstract: SummaryIn order to evaluate the general public's knowledge of postoperative pain and its management, a simple questionnaire was devised and sent out to five general practices in Scotland and Yorkshire. Questionnaires were completed voluntarily by 529 people attending their general practitioner for reasons not related to surgery. Five hundred and fifteen completed questionnaires were analysed. Two hundred and thirty-nine (46.4%) responders had undergone previous major surgery whereas 267 (51.8%) had not. Attitu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
32
0
3

Year Published

1998
1998
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(38 citation statements)
references
References 18 publications
3
32
0
3
Order By: Relevance
“…Similar to previous studies, our results indicate that patients having moderate to severe pain are satisfied with the management [3,6,[11][12][13]. Even patients saying they never had good pain relief were 83% satisfied (or very satisfied).…”
Section: Discussionsupporting
confidence: 79%
See 2 more Smart Citations
“…Similar to previous studies, our results indicate that patients having moderate to severe pain are satisfied with the management [3,6,[11][12][13]. Even patients saying they never had good pain relief were 83% satisfied (or very satisfied).…”
Section: Discussionsupporting
confidence: 79%
“…Interestingly, high satisfaction scores are reported regardless of pain intensities in a small number of studies performed on quality assessment of postoperative pain therapy. The fact that undertreatment of acute postoperative pain has been a source of fear of patients may partially explain the high incidence of satisfaction in these studies [1,5,8,12]. Besides, the immediate accessibility of analgesic agents, the more uniform level of analgesia inherent with PCA and the ability to titrate analgesia have been proposed as other possible explanations for the enhanced satisfaction associated with this technique.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Postoperative pain intensity was a decisive factor in patient satisfaction following day surgery in several studies [5,9,11,13,[23][24][25]. Both at discharge and 30 days after surgery, patients with lower postoperative pain scores were also the ones who reported higher satisfaction levels.…”
Section: Discussionmentioning
confidence: 93%
“…A British study of the impact of postoperative pain on women's experience and recovery following major gynecological surgery reported that patients have low expectations and inadequate coping strategies and knowledge of pain after discharge from hospital (Carr, 2001). Research exploring expectations of postoperative pain and its relief indicate that most people have little or no understanding of the nature of postoperative pain or of the methods available to treat it by themselves (Scott & Hodson, 1997). In our study, the women were advised by the hospital to take analgesics both regularly and PRN upon returning home.…”
Section: Discussionmentioning
confidence: 99%